Locked in a violent embrace understanding and intervening in domestic violence - Eisikovits, Zvi.; Buchbinder, Eli.; Sage eBooks (Thousand oaks, Calif. ; London : SAGE, 2000)
This study draws upon data from a series of qualitative studies and clinical practice with numbers of batterers and battered women. It focusses on couples who choose to remain together and make sense of their life together, in spite of violence.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wife abuse -- Israel; Abused women -- Israel; Abusive men -- Israel; Abused women -- Counseling of -- Israel; Abusive men -- Counseling of -- Israel; Electronic books